Role Education Political in Shaping Awareness Political in Faceissue Environment Life Global - Aulia Rahmah (International Journal of Students Education, 2024)
Indonesia is a country that is still vulnerable to conflict as a result difference. Where to overcome this, every citizen must understand regarding functions as a citizen, including understanding the necessary efforts to defend the country owned. This can be realized as early as possible through citizenship education through sector education formal. article this aim for learn how education citizenship which applied in environment school base can fostering an attitude of defending the country for students. This research uses the method qualitative and analytical descriptive approaches to discuss existing problems. data secondary sources are obtained from books, journals and also official online sites served for support analysis. Research result show that on basically citizenship education has competencies and a curriculum in the form of objectives must be fulfilled, namely to foster a sense of nationalism, understanding of rights and citizen obligations, values and morals, as well as implementation efforts to defend the country itself. Effort defend country which including into the character nationalism can fertilized and taughtto elementary school students in a good cognitive way through classroom learning, affective with teach and give an example, nor combined both of them with make learning creative and pleasant.